Empowerment of Marginalized Consumers Through Social Capital: Proposal of A Model And Profiles - Cucato, Jussara; Bizarrias, Flavio; Figueiredo, Júlio; Strehlau, Vivian (Future Studies Research Journal: Trends and Strategies, 2022)
Objective: The aim of this study is to determine how consumer empowerment, approximated by Social Capital, is influenced by the social adjustment function of attitudes and brand congruence with Self in consumers with a sense of power distance. Method: A survey was conducted with data analyzed using Structural Equation Modeling, with mediation analysis using Sobel's test, supplemented by a latent class analysis, to detail the consumer empowerment profiles in the study. Results: The results indicated that consumers with power distance may feel empowered when brands integrate into their identity conditionedon the social adjustment function of attitudes. However, this is less pressing for less empowered consumers. Conclusions: This study contributes theoretically to the consumer empowerment literature, particularly of vulnerable, absent consumers such as those represented by a power distance trait, by proposing a theoretical model for this integration.